Jerko Marasović’s Architectural Designing Achievements - Snježana Perojević (Prostor)
Jerko Marasović was an outstanding, internationally recognized expert in the field of architectural heritage. However, his designs for new architecture remain largely unknown. This paper aims to consolidate what is known about his lifelong work. Its objective is to analyze and contextualize his architectural contributions, which span the spectrum between Modernism and Critical Regionalism, within the framework of their development. All available graphic and textual materials related to the designs were studied and relevant literature was consulted. To support his affiliation with the direction of Critical Regionalism, this paper briefly presents its key features and discusses its relevance today. An analysis of Jerko Marasović’s designs revealed their generally high quality. He developed his concepts through a profound understanding of the layers and characteristics of Dalmatian architecture, as well as a consistent application of an analytical, rational, and responsible design process, in line with his own scientific ethos. By employing this approach, he created an architecture that can be classified as Critical Regionalism, even prior to the theoretical definition of that direction.